IMMUNOMODULATORY EFFECT OF SUBLETHAL DOSE OF CITRININ AND AFLATOXIN IN BROILER CHICKEN* - C. Theophilus Anand Kumar; C. Balachandran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was planned to find out the individual and combined immunomodulatory effects of sublethal doses of citrinin (CTN) (5 ppm) and aflatoxin (AF) (0.5ppm) in broiler chicken. Ninety-six newly hatched broiler chicks were randomly allotted to 4 groups of 24 birds each and fed with control, CTN (5 ppm), AF (0.5 ppm) and CTN (5 ppm) +AF (0.5 ppm) diets from 0 to 6 weeks of age. The birds were vaccinated against Newcastle disease (ND) virus on 7th and 28th day of age. The HI titres to ND vaccination and the stimulation index of splenocytes decreased significantly (P<0.05) in all the mycotoxin treated groups when compared to the control group. The present study indicated that CTN even at the sublethal dose level could lower the immune status of the birds and among the mycotoxin fed groups. AF played a more potential role in causing the reduction when compared to CTN.